Coastal Aquacultures and Mariculture - Athithan, S. (Abingdon, Oxon ; Boca Raton, FL : CRC Press, 2021)
This book is an effort to consolidate and comprehensively present the coastal aquaculture & mariculture and divided into39 chapters covering introduction, mariculture scenario, finfish farming, shellfish farming, molluscan farming, seaweed farming, recirculatory aquaculture systems, conservation aspects in mariculture etc. This is an attempt to provide comprehensive information on all areas of coastal aquaculture and mariculture to the students for their academic carrier. Nonetheless, the material presented has been thoughtfully selected and updated to make it of maximum use to the readers.Note: T& F does not sell or distribute the Hardback in India, Pakistan, Nepal, Bhutan, Bangladesh and Sri Lanka.
1 Introduction 2 Coastal Aquaculture and Mariculture -- Global scenario 3 Coastal Aquaculture and Mariculture -- Indian scenario 4 Coastal Aquaculture and Mariculture -- Meaning 5 Main objective and Main types of the mariculture 6 Integrated Multitrophic Aquaculture (IMTA) 7 Resources 8 Major Constraints in Mariculture 9 Diversification and Future Prospects 10 Traditional Fish Farming in India 11 Milk Fish Farming 12 Mullet Fish Farming 13 Pearl Spot Fish Farming 14 Silver Pompano Fish Farming 15 Culture of Silver Pompano in Coastal Aquaculture Ponds 16 Capture Based Aquaculture -- An Introduction 17 Capture Based Aquaculture of Red Snapper in Cages 18 Open Sea Cage Culture 19 Grow-out Culture of Finfishes and Management of Marine Cages 20 Development of Innovative Low Cost Cages for Promoting Open Sea Cage Culture 21 Sea Cage Farming of Cobia 22 Sea Bass Fish Farming 23 Marine Ornamental Fish Culture 24 Shrimp Farming 25 Lobster Fattening and Farming 26 Crab Farming and Fattening 27 Edible Oyster Farming 28 Pearl Oyster Farming and Pearl Production 29 Mussel Farming 30 Clam Culture 31 Scallop Farming 32 Sea Cucumber Farming 33 Horse Shoe Crab Farming 34 Sea Horse Farming 35 Abalone and Cephalopod culture 36 Seaweed Farming 37 Recirculatory Aquaculture Systems (RAS) 38 Artemia Cyst and Biomass Production 39 Good Practices in Coastal Aquaculture and Mariculture
OCLC-licensed vendor bibliographic record.
Keywords: Aquaculture; Mariculture; SCIENCE / Life Sciences / General; SCIENCE / Life Sciences / Biology / Marine Biology; TECHNOLOGY / Food Science